ATRIBUTOS DO SOLO EM ÁREAS COM TRÁFEGO CONTROLADO DE MÁQUINAS APÓS O CULTIVO DA SOJA - OLIVEIRA, Débora Cristina Sousa Barros de,; SANTOS, Maria Aparecida do Nascimentos dos,; GUIMARÃES JUNNYOR, Wellingthon da Silva,; SILVA, Fagner Luiz Rodrigues da,; MARTINS, Murilo Battistuzzi,; FERREIRA, Laura Martins1 (lauramartinsferreira45@gmail.com, (ANAIS DO ENIC, 2023)
-